Edible Safety Evaluation of Cinnamomum camphora Seed Kernel Oil: Sub-Chronic Toxicity and Teratogenicity Assessments - Xianghui Yan; Ting Peng; Zheling Zeng; Pengbo Wang; Yifang Gao; Xuefang Wen; Jiaheng Xia; Deming Gong; Ping Yu (Foods)
Medium chain triglycerides (MCTs) are regarded as an important ingredient for functional foods and nutraceuticals. Cinnamomum camphora seed kernel oil (CCSKO) contains more than 95% medium chain fatty acids (MCFAs), which is a significantly higher level than palm kernel oil (62%) and coconut oil (55%). However, the safety assessment of CCSKO, as the only natural MCT oil rich in capric acid and lauric acid found so far in the world, has not been fully verified. The study aimed to investigate the 90-day sub-chronic oral toxicity and teratogenicity of CCSKO. In the sub-chronic oral toxicity study, no clinically significant adverse events occurred in male or female Sprague–Dawley (SD) rats with CCSKO daily administration for 13 weeks. Moreover, there were no dose–response relationships between CCSKO and body-weight gain, food intake and food utilization in male or female SD rats. No significant differences (p > 0.05) were found in the hematological properties or organ weights between the male and female SD rats. In the teratogenicity test, no toxicological signs were observed in either Wister pregnant rats or fetuses. The no-observed-adverse-effect level of CCSKO was determined to be more than 4 mL/kg body weight. These results suggested that CCSKO may be an excellent edible oil with high oral safety.